Paroxysmal Nocturnal Dyspnea Secondary to Right Ventricular Myxoma: A Novel Presentation of an Unusual Tumor - Tristan E. Knight; Bruce Shiramizu; Princeton Ly; Karen S. Thompson; Venu Reddy (Hindawi Limited, 2018)
A 14-month-old male presented with paroxysmal nocturnal dyspnea and grade III/VI systolic ejection murmur at the upper left sternal border with an S4 gallop and was subsequently found to have a right ventricular cardiac myxoma. Prior presentations of these tumors have been with exertional syncope and murmur, asymptomatic murmur, or exertional dyspnea; the presentation of such a tumor with paroxysmal nocturnal dyspnea is novel.